Estratégias de controle químico do azevém na cultura da cevada - Tocha, Brenda Gross (Universidade Estadual de Ponta Grossa (UEPG), 2026)
With the aim of evaluating different herbicide management practices for ryegrass control and verifying their selectivity in barley, two experiments were conducted in two consecutive winter growing seasons, 2024 and 2025, at the Capão da Onça School Farm (FESCON) of the State University of Ponta Grossa. Both experiments used a randomized block design with four replications. The two experiments consisted of nine treatments: 1- S-metolachlor (960 g a.i. ha- 1); 2- Pyroxasulfone (125 g a.i. ha-1); 3- S-metolachlor + Pinoxaden (960 g a.i. ha-1 + 50 g a.i. ha-1); 4- Pyroxasulfone + Pinoxaden (125 g a.i. ha-1 + 50 g a.i. ha-1); 5- Pinoxaden (50 g a.i. ha-1); 6- S-metolachlor + (S-metolachlor + Pinoxaden) (480 g a.i. ha-1 + (480 g a.i. ha-1 + 50 g a.i. ha-1)); 7- Pyroxasulfone + (Pyroxasulfone + Pinoxaden) (62.5 g a.i. ha-1 + (62.5 g a.i. ha- 1 + 50 g a.i. ha-1)); 8- Infested control and 9- Weeded control. In the first experiment, ryegrass control was evaluated, and in the second, the selectivity of the treatments. The treatments were applied using a CO2 pressurized backpack sprayer. The travel speed was 1 m s-1, with a spray volume of 150 L ha-1. The variables evaluated in the first experiment were: ryegrass plant count per m2 at 15, 30, 45, and 60 (Days After Treatment - DAT), number of ears and ryegrass ear mass, as well as barley moisture, hectoliter weight (HLW), thousand grain weight (TGW), and productivity (kg ha-1). For the second experiment, the following were evaluated: plant height and dry weight of the barley aerial part at 45 DAT, moisture, HLW, TGW, and productivity. The data were subjected to analysis of variance using the RStudio program, and the means were compared using the Student-Newman-Keuls (SNK) and Dunnett tests at a 5% probability level. The results show that: regarding ryegrass control, the isolated application of Pyroxasulfone presents greater residual efficiency when compared to S-metolachlor; However, sequential management strategies or those combined with Pinoxaden result in higher and more persistent levels of control. In sandy soils, combined with adequate straw cover and rainfall regime, the herbicides S-metolachlor and Pinoxaden show greater selectivity to barley compared to Pyroxasulfone. However, the combination of Pyroxasulfone and Pinoxaden provides higher productivity values. In environments characterized by low straw cover associated with high rainfall, Pyroxasulfone may cause phytotoxicity symptoms; however, the crop demonstrates recovery capacity throughout the cycle, without compromising hectoliter weight (HLW), thousand-grain weight (TGW), and productivity.
Keywords: Pinoxaden; Pyroxasulfone; S-metolachlor; seletividade; controle